How to revive Doha with some chance of success - Roderick Abbott (European Centre for International Political Economy (ECIPE), 2009)
This Policy Brief concerns the troubled state of the Doha Round. The classical model for a multilateral trade negotiation (as developed from the GATT years and commonly called a Round) would include trade liberalisation through tariff reductions and elimination of non-tariff barriers, with an expectation of active participation by around 40 countries who would collectively account for 90% of world trade. Many GATT members were thus peripheral to the process. Among other consequences this led to skewed results with much less progress in areas where developing countries had a major interest, but where the main players had a defensive attitude such as agriculture and textiles.
Keywords: 330; Internationale Handelspolitik; WTO-Recht; Welt